PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PRODUKSI PT HASTA PUSAKA SENTOSA PURBALINGGA - Barima, Hima; Puspitawati, Endah; Supriatin, Dyah (UNPERBA, 2025)
Human resources are the most important asset of the company, therefore to improve the efficiency and productivity of the company, the company has the responsibility to improve the quality of productivity of its human resources. Work motivation and work discipline is one of the solutions to improve HR productivity. Work productivity can be influenced by internal and external factors, so leaders who are able to motivate are needed. This study aims to determine the effect of work motivation and work discipline on the work productivity of production workers in PT Hasta Pusaka Sentosa Purbalingga. The sampling technique in this study used simple random sampling technique, namely random sampling technique in the population and the research sample using the Slovin formula so that the research sample became 77 people. The results of the study partially show that work motivation has no effect on employee productivity, while partially show that work discipline affects employee productivity. While simultaneously work motivation and work discipline affect employee productivity. The implications of the previous research motivation has a positive and significant effect while work motivation also has a positive and significant effect.